CONFLICT OF AQUATIC RESOURCES AND ITS UNDERLYING CAUSES: A CASE STUDY FROM DONAN RIVER AREA, SEGARA ANAKAN REGION, CILACAP, CENTRAL JAVA - Taufik Budhi Pramono (Jurnal Kelautan, 2009)
This research aimed to know internally conflict on the use of aquatic  resources at around Donan River, Segara Anakan region Cilacap.  Using on fisheries resources was not free against potential conflict among the user or with its interest’s one related to that resources.  The lack on capability of identified conflict would be a limiting factor for the implementation on the fisheries resources management program.  The research was hold in the region of Segara Anakan, Donan River from August until October 2005.  The data collection techniques applied in this survey included questionnaire; observation; in-depth interview with leaders of fisherman organizations; and focus group discussion. Quantitative data was analyzed by descriptive statistics.  The research showed that fisherman’s community along Donan River line were not out of inside potentially conflict among inter micro-micro, intra micro-micro and intra micro-macro.  This potential conflict were appeared because of presence on the different perception belong to its authority access against Donan River and their open system on the fisheries resources management.Keywords : Conflict, Donan River, Aquatic Resources, Fisherman Community